High Prevalence of Plasminogen Activator Inhibitor-1 4G/5G Polymorphism among Patients with Venous Thromboembolism in Kerala, India - Tony, Ann Maria; Vinod, Vivek; Nambiar, Vivek; Krishnan, Sajitha; Biswas, Lalitha (Hämostaseologie, 2022)
Venous thromboembolism (VTE) is a multifactorial clotting disorder in which inherited and environmental factors synergistically contribute to its pathogenesis. The aim of this case–control study was to analyze the prevalence of hereditary thrombophilic risk factors, provoking and non-provoking environmental risk factors in patients with VTE from Kerala, India. We have observed a low prevalence of factor V Leiden (7%), prothrombin G20210A (2%), and prothrombin G20030A (2%) mutations and a high prevalence of plasminogen activator inhibitor-1 (PAI-1) 4G/5G (52%), PAI-1 4G/4G (24%) genotypes in the VTE patients (n = 147). Deficiency of anticoagulants, antithrombin (3.4%), and protein C (4.1%) was relatively low. None of the risk factors were observed in 17% of the patients. Majority of VTE patients were younger than 50 years with a median age of 43 years. In conclusion, our results indicate a high prevalence of PAI-1 4G/5G polymorphism among the VTE patients which is in concordance with previous studies in the Asian population. The PAI-1 4G/5G polymorphism could be a potential biomarker for assessing VTE risk, particularly among the Indian population.
Keywords: venous thromboembolism; risk factors; MTHFR C677T; factor V Leiden; plasminogen activator inhibitor-1; prothrombin gene; C-reactive protein; genetic mutations